2016
DOI: 10.1163/2451-8921-00103002
|View full text |Cite
|
Sign up to set email alerts
|

How Do Governors Build a Power Vertical in the Context of Mayoral Elections?

Abstract: Although the spread of direct mayoral elections was weakened during the 2000s, they have survived in many municipalities until the present time. In the context of Russia’s ‘power vertical’, regional authorities are strongly involved in local elections. As a rule, they have their own candidates and provide them with support during election campaigns. It is not surprising that most often the candidates of governors are incumbents. At the same time, there are many cases when a governor prefers not to support an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This variation in influence has formed a sort of de facto decentralization, as governors which are more influential in Moscow may act in a more independent (decentralized) manner on various policies and may have greater power in swaying even more local election process such as mayoral contests (Panov 2016).…”
Section: …And the Russian Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…This variation in influence has formed a sort of de facto decentralization, as governors which are more influential in Moscow may act in a more independent (decentralized) manner on various policies and may have greater power in swaying even more local election process such as mayoral contests (Panov 2016).…”
Section: …And the Russian Approachmentioning
confidence: 99%
“…This variation in influence has formed a sort of de facto decentralization, as governors which are more influential in Moscow may act in a more independent (decentralized) manner on various policies and may have greater power in swaying even more local election process such as mayoral contests ( Panov 2016 ). Such an effect already has some evidence: Beazer (2015) , examining economic performance in various parts of Russia, showed that regions which had little political competition pre-reform were bolstered by the newfound favor shown by the center and saw better economic outcomes.…”
Section: …And the Russian Approachmentioning
confidence: 99%
“…Yet there is also a requirement that is absent in legislative elections, locally referred to as the 'municipal filter', according to which anyone wishing to register as a candidate for a gubernatorial election has to collect a number of signatures from a specific number of members in a specific number of regional and/or municipal assemblies. Given that United Russia holds overwhelming majorities in most of these bodies and that the inferior standing of these bodies in Russia's system of governance makes their members heavily dependent on regional authorities (Panov, 2016), it is generally recognized that, with a partial exception of the KPRF, all candidates nominated by other parties are capable of passing through the 'municipal filter' only if the incumbent governor authorizes the municipal deputies to supply such candidates with sufficient numbers of signatures (Blakkisrud, 2015;Epstein, 2014). This practically prevents from running any candidate who is perceived as posing a real challenger to the acting governor.…”
Section: The Interplay Of Authoritarian Dominance and Quasi-democratimentioning
confidence: 99%